Instructors' beliefs on critical thinking and their classroom practices: a case study / Nurul Ain Hasni - Hasni, Nurul Ain (2014)
The ability to think critically is an essential life skill which needs to be developed in order to compete in a global environment. Current literature reveals that explicit critical instruction, and practice of critical thinking (CT) strategies helps to improve learner’s performances. Hence, it is vital for instructors to have strong beliefs in critical thinking as it influences their classroom practice. The present study seeks to fill the gap between instructors’ beliefs as well as practices which serves to be important in improving the educational process. The aim o f this study was to investigate how instructors perceived CT as well as their classroom instruction in teaching the skills among tertiary level learners. Further, it also investigates whether the constructs (beliefs and practices) of the instructors matched with one another. The participants of this study involved instructors from Universiti Teknologi MARA (UiTM) located in Sri Iskandar Perak. Data were collected using exploratory qualitative approach and the findings were presented in a qualitative descriptive approach through interviews as well as observations. Findings revealed that both instructors had indicated their own beliefs which reflect general concept of CT that is acceptable and relevant to their field of scope. Also, both instructors’ CT instructions reflect higher-order thinking that mostly requires learners to use their thinking. It could be synthesized that what they believed about CT skills seem to match with what they practiced. Overall, instructor of graphic design (GD) had more explicit fostering of CT where learners appeared to be reaping and engaged with the skills more indepth compared to English writing class. This is due to the nature of the field (GD) which requires CT skills in the course subject. Based on the findings, this study also provides implications for pedagogy and practice as well as recommendation for improvement of practices and future research.